P231 CPR and Ventilation Preferences in COPD Patients Using Home NIV: Still Unexplored After Ten Years. (19th November 2012) - Dickson, JL; Gadhok, R; Hind, MD; Simonds, AK; Polkey, MI
Abstract : Introduction: The GMC, NCEPOD and Resuscitation council UK have clear guidelines suggesting early decision making when considering appropriateness of CPR and invasive ventilation (ETV) in acute admissions. Furthermore patient preferences should be identified in advance of acute deterioration where they have an existing condition that makes cardiac or respiratory arrest likely. It is currently unclear how closely this advice is followed in practise. Since COPD patients requiring home ventilation have higher than average risk of acute respiratory failure and death 1 we reasoned that CPR/ETV should have been discussed in all cases, but in 2002 a prior audit found that such discussion was infrequent. Aim: Re-audit, ten year interval using the same survey to assess whether there had been improvement in practise and also re-evaluate patients' preferences. Method: Eight question survey in our home ventilation clinic selecting 20 patients with severe COPD on domiciliary non-invasive ventilation. Results were compared to those of 19 similar patients from 2002. Statistical differences were explored with the fishers-exact test. Results: The proportion of patients who had been asked about CPR/ETV preferences had not improved between 2002 and 2012; 4/19 (21.1%) in 2002 and 7/20 (35%) in 2012 (p=0.54) and remained unacceptably high. The majority of patients wanted more opportunity to discuss their preferences; 17/19 (89.5%) in 2002 and 11/20 (55.0%) in 2012 (p=0.038). In both 2002 and 2012, patients' preferences for CPR/ETV were influenced by the likelihood of survival but a significant minority wished to receive these therapies even with a quoted chance of survival <1% or negligible (figure 1 ). Discussion: Despite ten years awareness of the issue, our institution had failed to significantly improve CPR/ETV discussions in COPD patients attending the home ventilation clinic. We found that people frequently had their own views regarding CPR/ETV and most people would like the opportunity of further discussion. The trust wide use of DNAR forms has not sufficiently improved practise. We believe that the use of a trust wide resuscitation status form might improve this outcome. Divo M et al. Comorbidities and Mortality Risk in Patients with COPD. Am J Respir Crit Care Med. April 2012.